Income inequality in Europe: Reality, perceptions, and hopes - Alessandra Faggian; Alessandra Michelangeli; Kateryna Tkach (Research in Globalization, 2023)
Is actual income inequality accurately translated into people's perceptions, and what are the genuine hopes of citizens? Our contribution offers insights into how the reality and two subjective dimensions of income inequality, namely perceptions, and desires, interact. Using data from the Eurobarometer, we study the main patterns of different "types" of inequality (measured by S80/S20 ratio) in the regions of the EU Member States. Considering the role of attitudes and beliefs, the residents of the same region are typically found to hold a similar perception of how unequal their society is. Moreover, and somewhat surprisingly, the reality is contrary to people's perception since low (high) actual income inequality in the region is often reflected in its overestimated (underestimated) perception. We also show that perceived, and desired inequality are distinct metrics as commonly applied determinants of perceptions are rather weakly associated with desired inequality, probably due to the normative nature of the latter. The evidence presented here implies that objective measures of income inequality should be used in conjunction with subjective ones to gain a complete picture of the phenomenon. Our findings may assist policy-makers and other interested stakeholders in designing dedicated policies to counteract inequality in all its forms.
Keywords: D31; D63; D83; I31; 330; Desired inequality; Europe; Income inequality; Income quintile share ratio; Inequality perceptions